2008
DOI: 10.1016/j.bbmt.2008.02.012
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Hematopoietic Stem Cell Transplantation: Progress toward Clinical Application

Abstract: In utero hematopoietic stem cell transplantation (IUHCT) is a potential therapeutic alternative to postnatal hematopoietic stem cell transplantation (HSCT) for congenital hematologic disorders that can be diagnosed early in gestation and can be cured by HSCT. The rationale is to take advantage of normal events during hematopoietic and immunologic ontogeny to facilitate allogeneic hematopoietic engraftment. Although the rationale remains compelling, IUHCT has not yet achieved its clinical potential. Achieving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(109 citation statements)
references
References 111 publications
0
109
0
Order By: Relevance
“…Since the seminal experiments of Billingham, Brent, and Medawar (1), animal models of in utero hematopoietic cell transplantation (IUHCTx) have shown that the fetal environment offers considerable advantages for the success of stem cell transplantation (reviewed in ref. 2). In the mouse model, fetal mice can be tolerized to fully allogeneic stem cells without any immunosuppression (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Since the seminal experiments of Billingham, Brent, and Medawar (1), animal models of in utero hematopoietic cell transplantation (IUHCTx) have shown that the fetal environment offers considerable advantages for the success of stem cell transplantation (reviewed in ref. 2). In the mouse model, fetal mice can be tolerized to fully allogeneic stem cells without any immunosuppression (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Still, the risk of graft versus host disease is not completely ruled out by the IUT approach and could be a concern for human studies, although we have not experienced this adverse effect in our mice and its occurrence in the 50 reported human trials was not high. 13 In the present work, we compare the results obtained with fetal liver cells to those previously obtained with whole adult bone marrow. We want to emphasize that, although performed sequentially, the two set of experiments with the two different kinds of donor cells used the same strain and were evaluated in an identical way, thus making the comparison meaningful.…”
Section: Discussionmentioning
confidence: 56%
“…23 On the other hand, at variance with primary immunodeficiency, whose symptoms do not develop before birth, osteopetrosis would greatly benefit from IUT and, even if only partial engraftment is obtained, the patients could still be treated with postnatal transplantation with minimal ablation using cells from the same donor, as suggested by other groups. 13 An additional unexpected finding was that, even with transplants that are apparently totally successful, sclerotic bone occurs in a highly localized, random regions, including microscopic regions of sclerotic bone associated with malocclusion. This suggests that, at least in mice, osteoclast differentiation reflects mainly cells from local colonies of precursors, so that clonal variation can cause patches of sclerotic bone in animals rescued by intrauterine transplant that have grossly normal skeletons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, fetal transfusions and in utero stem cell-based therapies have now been performed clinically by numerous investigators for decades, using a variety of protocols, in efforts to treat patients with a number of different diseases [61,62]. While the stem cell trials have thus far only proven clinically successful in patients with immunodeficiencies, they have also demonstrated that accessing the early gestational human fetus multiple times poses minimal risks with modern imaging and ultrasound-guided delivery procedures [63]. Furthermore, it is important to note that experience and knowledge gained from studies performed in the fetal sheep model were used to design and perform the first curative human in utero transplantation for X-SCID [64], highlighting the value of the fetal sheep model for not only developing clinically viable methodology, but also for predicting clinical outcome.…”
Section: Rationale For Performing Gene Therapy In Uteromentioning
confidence: 99%